PENGARUH KOMPENSASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA PT. PUTRA SINAR GAS - Aprian Jopa; Melda Wiguna (Journal of Research and Publication Innovation, 2024)
With the rapid development of the industry, business organizations must be able to compete for the sustainability of business operations. Quality human resources are indispensable in carrying out company activities. The purpose of this study is to find out the Influence of Compensation and Leadership Style on Employee Performance at PT Putra Sinar Gas. The method used was quantitative with a sampling technique using saturated sampling and a sample of 50 respondents was obtained. Data analysis uses validity test, reliability test, classical assumption test, regression analysis, determination coefficient and hypothesis test. The results of this study are that Compensation (X1) affects employee performance (Y) with a determination coefficient value of 0.581 or 58.1% and the hypothesis test is obtained by calculating t > t table (8,160 > 2,012). Leadership Style (X2) had a significant effect on employee performance (Y) with a determination coefficient value of 0.384 or 38.4% and the hypothesis test was obtained by t calculation > t table (5,465 > 2,012). Leadership Style (X1) and Work Discipline (X2) had a significant effect on employee performance (Y) with a determination coefficient value of 0.585 or 58.5% and the hypothesis test was obtained F count > F table (33,144 > 3,190).